Autism Link to Herpes Simplex Virus 2 Antibody in Pregnancy Likely To Be Spurious - Magaret, Amalia S.; Wald, Anna (mSphere, 2017)
[...]the immunoassay used in this study is intended for qualitative diagnosis of Toxoplasma gondii, Rubella, cytomegalovirus, and HSV-1 and -2 (ToRCH) infections and not for comparison of quantitative antibody levels (2). Nearly 15% of women of childbearing ages are estimated to be HSV-2 seropositive globally (3). [...]an astounding number of women globally will experience a pregnancy while HSV-2 seropositive.